PENGEMBANGAN E-LKPD IPA BERBASIS LITERASI SAINS MATERI CAHAYA DI SEKITAR KITA UNTUK KELAS V SD NEGERI 161 PEKANBARU - Aulia Tika Utami; Dea Mustika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Teaching materials are an important component in supporting the learning process. This study aims to develop an Electronic Student Worksheet (E-LKPD) for Science based on scientific literacy on the subject of Light Around Us, to determine the level of product feasibility through expert assessments and teacher and student responses to the developed product. The research method used is Research and Development (R&D) with a 4D model limited to the development stage. Data collection techniques involve validation questionnaires by material experts, media experts, language experts, and teacher and student response figures. The results of the study indicate that the developed E-LKPD is very feasible to use with an average feasibility score from material experts of 95.8%, media experts 94.95%, and language experts 94.15% with a very feasible category. The results of teacher responses obtained an average of 97.45%, and student responses obtained an average of 92.5% with a very feasible category. Based on these results, it can be concluded that the E-LKPD for Science based on scientific literacy on the subject of Light Around Us is very feasible to use as a teaching material in science learning for grade V of elementary school.